Aggressiveness and Redistribution - Dieter Bös; Martin Kolmar (University of Bonn, Bonn Graduate School of Economics (BGSE), 2003)
In this paper we deal with voluntary and compulsory redistribution in an economy where the enforcement of property rights is costly. Two agents engage in a common-pool contest and two types of potential distortions arise: the waste of resources in the contest and the dilution of incentives to produce as a result of the existens of externalities in the conflict equilibrium. We were able to show the following results: (i) In some situations Pareto-improving redistribution occurs voluntarily. (ii) Otherwise, the government may choose an indirect way to improve production in the presence of appropriation: In a situation of partial anarchy in some market redistributive policies in other markets may help to reduce the inefficiency in the anarchic market.
Keywords: D30; D74; D23; 330; Anarchy; Contests; Redistribution; Einkommensumverteilung; Verteilungskonflikt; Spieltheorie; Eigentumsrechtstheorie; Anarchie; Theorie